Walter Benjamin and Bertolt Brecht the story of a friendship - Wizisla, Erdmut 1958- (Yale University Press, 2009)
"Erdmut Wizisla?s groundbreaking work explores for the first time the important friendship between Walter Benjamin, the acclaimed critic and literary theorist, and Bertolt Brecht, one of the twentieth century?s most influential theater artists, during the crucial interwar years in Berlin." "From the first meeting between Benjamin and Brecht and their roles in the ideological debate leading up to World War II, to their experiences in exile and Benjamin?s reaction to Brecht?s death, the events in this friendship are illuminated by the use of personal correspondence, journal entries, and notes - including previously unpublished materials- from the friends? electric discussions of shared projects. In addition to exploring correspondence between the two, Wizisla presents documents by colleagues who shaped and shaded their relationship, including Margaret Steffrin - Brecht?s assistant and lover - Theodor Adorno, and Hannah Arendt." "Wizisla shows us the fascinating ideological exchanges between the two, with Benjamin espousing his ideas on historical materialism, German idealism, and Jewish mysticism as a foil for Brecht?s Marxist concept of art. Their differences foreshadowed the clash between Communism and Socialism in Weimar Germany that preceded the rise of the Nazi Fascism. Wizisla?s examination of the friendship between Benjamin and Brecht, two artists at the height of their creative powers during a time of great political crisis, throws light on nearly two decades of European intellectual life."--BOOK JACKET.